Association of cerebrospinal fluid tap‐related oscillatory activity and shunt outcome in idiopathic normal‐pressure hydrocephalus. Issue 3 (27th April 2015) - Ikeda, Shunichiro; Kazui, Hiroaki; Tanaka, Toshihisa; Ishii, Ryouhei; Aoki, Yasunori; Hata, Masahiro; Canuet, Leonides; Yoshiyama, Kenji; Iwase, Masao; Pascual‐Marqui, Roberto; Takeda, Masatoshi
Abstract Background Idiopathic normal‐pressure hydrocephalus (iNPH) is a neuropsychiatric syndrome characterized by the clinical triad of gait disturbance, urinary dysfunction, and cognitive impairment. The aim of the present study was to find specific EEG patterns associated with shunt response in iNPH. Methods Twenty five iNPH patients (10 shunt responders and 15 non‐responders) were enrolled in this study. We performed current source density (CSD) analysis in several frequency bands (delta: 2–4Hz, theta: 4–8Hz, alpha: 8–13Hz, beta: 13–30Hz, gamma: 30–60Hz) using exact Low Resolution Brain Electromagnetic Tomography (eLORETA). CSD distribution was compared between shunt responders and non‐responders for each frequency band before and after CSF tap test. Results Shunt responders showed increased gamma CSD in the left temporal cortex before CSF tapping relative to non‐responders. However, after CSF tapping, shunt response was associated with significantly higher CSDs in several frequency bands, specifically theta, alpha, beta and gamma, involving mainly the frontal and temporal areas. Using eLORETA analysis, we were able to identify cortical oscillatory activity before and after CSF tap test related to clinical recovery due to shunt operation in iNPH. Conclusion Our findings support and extend the results of previous studies examining the effects of CSF tap test and shunt operation in patients with iNPH, possibly indicating electrophysiological features of shunt response in this disease. These findings warrant future studies to use EEG for prediction of shunt response in iNPH.